Interplay between topology and dynamics in excitation patterns on hierarchical graphs - Hütt, Marc; Lesne, Annick (Frontiers in Neuroinformatics, 2009)
In a recent publication [Müller-Linow et al. (2008) PLoS Computational Biology 4, 1000190] two types of correlations between network topology and dynamics have been observed: waves propagating from central nodes and module-based synchronization. Remarkably, the dynamic behavior of hierarchical modular networks can switch from one of these modes to the other as the level of spontaneous network activation changes. Here we attempt to capture the origin of this switching behavior in a mean-field model as well in a formalism, where excitation waves are regarded as avalanches on the graph.